Menakar Fungsi Izin Dan Mediasi Pada Sengketa Perceraian Di Kalangan Pegawai Negeri Sipil Kota Mataram Dari Tahun 2010-2020 - Muhammad Idrus (Indonesian Journal of Shariah and Justice, 2021)
Divorce is one of the events in a marriage that is religiously possible. For Muslims the case of divorce is halal but hated by "Allah SWT". For Civil Servants (PNS) Divorce can be done by the mechanism that has been regulated in the Law. One of them is the permit obtained and the stage of mediation that must be done, but in practice there are still many technical obstacles related to the implementation of divorce permits for civil servants, this is certainly a concern for many parties. This research then examines the function of permits and mediation in divorce disputes among civil servants, although the purpose of the required divorce permit is actually in order to complicate (prevent) the occurrence of divorce in the scope of civil servants, this study examines divorce permits and mediation stages for civil servants who are divorced in Mataram city from 2010-2020. By using qualitative methods combined with normative studies.